Penguatan Kesadaran Hak dan Kewajiban melalui Program Edukasi di Lapas Narkotika Kelas IIA Pamekasan - Achmad Taufik; Abdul Bari; Fredy Yunanto; Hasbullah Hasbullah; Rini Aristin; Muhammad Darrin Zuhri (Lembaga Pengembangan Kinerja Dosen, 2024)
The educational program “Strengthening Awareness of Rights and Obligations through an Educational Program at Class IIA Pamekasan Narcotics Prison” aims to improve the understanding of prisoners regarding their rights and obligations in the context of prison guidance. Implemented at Class IIA Pamekasan Narcotics Prison, the program integrates a participatory-based educational approach with materials covering basic rights, legal protection, and responsibilities as prisoners. Methods used include lectures, group discussions, and case simulations, with evaluation conducted through surveys and interviews. The results of the program showed a significant increase in prisoners' awareness of their rights and obligations, as well as positive changes in behavior and participation in prison activities. Challenges encountered include limited resources and initial resistance from some participants. However, the success of this program shows great potential for improving the quality of rehabilitation in prisons. Recommendations for similar programs include improved educational materials and adaptation for other prisons to expand the positive impact. This program makes an important contribution to the development of more effective and humane coaching practices in prison settings.